Changes to the criminal regulations introduced by the Marijuana Market Regulation and Control Law approved in Uruguay (2017)
The article reports on the evolution of the Uruguayan criminal law on drugs until the adoption of the current scheme, which introduces transcendent changes in the criminal figures regarding illicit drugs in general, as well as particularly regarding regul